Family History Assessment: Impact on Disease Risk Perceptions - Wang, Catharine (2012)
BACKGROUND: Family Healthware(™), a tool developed by the CDC, is a self-administered web-based family history tool that assesses familial risk for six diseases (coronary heart disease, stroke, diabetes, and colon, breast and ovarian cancers) and provides personalized prevention messages based on risk. The Family Healthware Impact Trial (FHITr) set out to examine the clinical utility of presenting personalized preventive messages tailored to family history risk for improving health behaviors. PURPOSE: The purpose of this study was to examine the impact of Family Healthware on modifying disease risk perceptions, particularly among those who initially underestimated their risk for certain diseases. DESIGN: A total of 3786 patients were enrolled in a cluster-randomized trial to evaluate the clinical utility of Family Healthware. SETTING/PARTICIPANTS: Participants were recruited from 41 primary care practices among 13 states between 2005 and 2007. MAIN OUTCOME MEASURES: Perceived risk for each disease was assessed at baseline and 6-month follow-up using a single-item comparative risk question. Analyses were completed in March 2012. RESULTS: Compared to controls, Family Healthware increased risk perceptions among those who underestimated their risk for heart disease (15% vs 9%, p<0.005); stroke (11% vs 8%, p<0.05); diabetes (18% vs 11%, p<0.05); and colon cancer (17% vs 10%, p=0.05); but not breast or ovarian cancers. The majority of underestimators did not shift in their disease risk perceptions. CONCLUSIONS: Family Healthware was effective at increasing disease risk perceptions, particularly for metabolic conditions, among those who underestimated their risk. Results from this study also demonstrate the relatively resistant nature of risk perceptions. TRIAL REGISTRATION: This study is registered at clinicaltrials.gov NCT00164658.